A fair price for energy? Ownership versus market opening in the EU15 - Carlo V. Fiorio; Massimo Florio (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the past two decades privatisation and liberalisation of network industries providing services of general economic interest (SGEI), have been particularly significant in the European Union. Wide variations around a common policy trend can, however, be observed across countries and sectors. We focus on electricity and gas sectors because energy sectors have usually been profit makers, not affected by direct government transfers, in contrast to other SGEI. We study the effects of privatisation and other reforms on consumer prices using both subjective data on consumers' perception of utility prices and data on average prices paid.
Keywords: L94; L95; L33; 330; privatisation; electricity; gas; reforms; Stromtarif; Gaspreis; Elektrizitätswirtschaft; Gaswirtschaft; Privatisierung; Deregulierung; EU-Binnenmarkt; Wirkungsanalyse; EU-Staaten